Faktor yang mempengaruhi pembayaran zakat di syarikat tersenarai awam di Malaysia / Adibah Ab Wahab - Adibah, Ab Wahab (2016)
Zakat is one of the main religious dues in Islam. Zakat does not only purify one’s wealth but also a mechanism to uplift the socio-economy of the ummah. According to National Fatwa Committee, business entities which formed under principle of syakhsiyyah i’tibariyyah (legal entity) are obliged to pay zakat under the the principle of khultah (group ownership). However, factors which influence business entity’s zakat payment are still not properly defined and very limited researches done on this. The aim of this research is to identify zakat payment influencing factors in business entities and take Public Listed Companies (PLCs) as research subject and decision makers in PLCs as research object. Through mixed-method research design, this study uses secondary data, interviews and questionnaires. Secondary data from PLC annual reports are used to understand the scenarios, estimates potential zakat collection and identify the collection gap for this market segment. From 817 shariah-compliant listed companies, 118 companies have more than 30% muslim ownership and 17 companies pay zakat. From the analysis, total zakat potential is RM291.5 million and the collection gap is RM215 million a year (74%). Based on qualitative data from interviews with 14 companies and quantitative data from 113 questionnaires (13 companies), the study reveals three main factors that influence zakat payment by business entity, i.e. effort done by zakat institution (Zakat Institutional Role), action taken by government (Government Action) and companies’ own initiative (Internal Motivation). The result indicates that Zakat Institutional Role has three sub factors i.e. services provided by the institution, zakat disbursement program and good governance. As for Government Action there are three underlying sub factors i.e. fatwa ruling, tax incentives either in the form of rebate or deduction and legal enforcement. Internal Motivating factor also has three sub factors i.e. board directors understanding, muslim board director composition in the company and financial performance. Internal Motivation is the most influential factor with the highest significance value. It plays important role as the mediating factor between Zakat Institutional Role and Government Action with zakat payment. All variables and their relationships are explained in a schematic path diagram called Zakat Payment Model for Business Entity. This hierarchical model is evaluated and assessed following Partial Least Squares - Structural Equation Modelling (PLS-SEM) procedures, i.e. measurement model, structural model and mediator analysis. In conclusion, this study successfully provides empirical evidence on potential zakat collection in PLC segment and the influencing factors for business entity zakat payment. This study contributes to the theory, literature and insight on factors affecting zakat payment by business entity particularly for PLCs and provides better understanding of current scenarios on potential zakat collection in PLC market segment in Malaysia.